Hydrogeology of Brahmaputra Basin, India (Journal of Nepal Geological Society, 2003)
The Ganga-Brahmaputra river system together forms one of the largest deltas in the world comprising some 59570 sq km. The waterpower resources of the Brahmaputra have been presumed to be the fourth biggest in the world being 19.83 x 103 m3s1. The entire lower portion of the Brahmaputra consists of a vast network of distributary channels, which are dry in the cold season but are inundated during monsoon. The catchment area of the entire river is about 580,000 sq km, out of which 195,000 sq km lies in India. The maximum discharge as measured at Pandu in 1962 was of the order of 72800 m3 s-1 while the minimum was 1750 m3 s-1 in 1968. The drainage pattern in the valley is of antecedent type while the yazoo drainage pattern is most significant over the composite flood plain to the south of the Brahmaputra.The Brahmaputra valley is covered by Recent alluvium throughout its stretch except a few isolated sedimentary hills in the upper Assam, inselbergs/bornhardt of gneissic hills in the Darrang, Kamrup and Goalpara districts and a few inlying patches of Older Alluvium in the Darrang and Goalpara districts.The basin is very unstable. The present configuration of the basin is the result of uplift and subsidence of the Precambrian crystalline landmasses. Four geotectonic provinces can be delineated in the N-E India through which the Brahmaputra flows. These are bounded by major tectonic lineaments such as the basement E-W trending Dauki fault, a NE-SW trending structural feature of imbricate thrusts known as 'belt of Schuppen' and the NW-SE trending Mishmi thrust.Hydrogeologically, the Brahmaputra basin can be divided into two distinct categories, viz(a) dissected alluvial plain and (b) the inselberg zone. The first category is rep resented in the flood plain extending from the south of Sub-Himalayan piedmont fan zone in the north to right upto the main rock promontory of Garo Hills and Shillong Plateau. The inselberg zone is characterized by fractured, jointed and weathered ancient crystalline rocks with interhill narrow valley plains, consisting of thin to occasionally thick piles of assorted sediments.From the subsurface lithological data, two broad groups of aquifers are identified. These are i) shallow water table and ii) deeper water table or confined ones, separated by a system of aquicludes. The shallow aquifer materials, in general, consist of white to greyish white, fine grained micaceous sand and the thickness ranges from 1.2 to 10.3 m. The sand and clay ratio varies from 1: 2.5 to 1:26. The bedrock occurs at depth ranges of 30.4 to 39.5 m. The materials of the deeper aquifers comprise grey to greyish white, fine to medium grained sand. The sand and clay ratio varies from 1:2 to 1:7. The effective size of the aquifer materials varies from 0.125 to 0.062 mm with uniformity co-efficient around 4.00, porosity 38 to 42%, co-efficient of permeability 304 to 390 galls per day/0.3m2. The ground water is mildly alkaline with pH value 6.5 to 8.5, chloride 10 to 40 ppm, bi-carbonate 50 to 350 ppm, iron content ranges from a fraction of a ppm to 50 ppm. Total dissolved solids are low, hardness as CaCo3 50 to 300 ppm, specific conductance at 25 °C 150 to 650 mhos/cm. The yield from shallow aquifers is 1440 litres to 33750 litres/hour and for deeper aquifers ~ 1700 litres/hour at a drawdown of 13.41 m, specific capacity 21 litres/minute. The temperatures of ground water are 23°-25° C during winter, 24°-26° C during pre-monsoon and 27°- 28° C during peak monsoon. The general hydraulic gradient in the north bank is 1:800 whereas in the south bank it is 1: 300-400 The Tertiary sediments yield a range of water from 200 to 300 l.p.m whereas the yield from the Older Alluvium is 500 to 700 1.p.m. The estimated transmissibility and co-efficient of storage is of the order of ~ 800 1.p.m/ m and 8.2 x 10-3 respectively. Depths to water levels range from 5.3 to 10m below land surface (b.l.s). In the Younger or Newer Alluvium, ground water occurs both under water table and confined conditions. Depths to water levels vary from ground level to 10 m b.l.s. Depth to water ranges from 6 m b.l.s. to 2 m above land surface. The yield of the deep tubewells ranges from 2 to 4 kl/minute for a drawdown of 3 m to 6 m. The transmissibility of the aquifers varies from 69 to 1600 l.p.m/m and the storage co-fficient is of the order of 3.52 x 10-2.